Engaging Duterte: That Space in Between Populism and Pluralism - Abao, Carmel V (Archīum Ateneo, 2017)
With essays by leading experts in diverse fields, this book offers a penetrating portrait of a volatile administration poised between a troubled past and an uncertain future. The research is thorough; the writing eloquent; and the insights myriad. This is critical reading for anyone who wishes to understand this perplexing moment in the ever-changing, ever-fascinating politics of the Philippines.— Alfred W. McCoy, author of In the Shadows of the American Century: The Rise and Decline of US Global Power This book offers timely, incisive, and well-grounded analyses of the rise of Rodrigo Duterte from child of a crisis-prone postcolony wracked by intense intra-elite electoral competition, revolutionary challenges from various sectors of society, and authoritarian rule and top-down developmentalism to long-time mayor of Davao and first Mindanaoan president of the Philippines.— Caroline S. Hau, author of Elites and Ilustrados in Philippine Culture The irony doesn’t escape us: A Duterte Reader packs a lot of rigorous thinking into its pages to give coherence to a man who eschews rigor and downgrades facts. Still, public intellectuals cannot shirk from their civic duty to civilize the national conversation.— Marites D. Vitug, author of Shadow of Doubt: Probing the Supreme Court